Effect of manure and NPK to increase soil bacterial population of Azotobacter and Azospirillus in chili (Capsicum annum) cultivation - MUJIYATI MUJIYATI; SUPRIYADI SUPRIYADI (Nusantara Bioscience, 2009)
Mujiyati, Supriyadi. 2009. Effect of manure and NPK to increase soil bacterial population of Azotobacter and Azospirillum in chili (Capsicum annum) cultivation. Nusantara Bioscience 1: 59-64. The objectives of this research were to find out the increase number of two bacterials populations, Azotobacter and Azospirillum, due to the use of manure fertilizer. The exsperiment was conducted using group randomly designed with two treatments. The plant populations were treated (i) whithout fertilizer as the control, (ii) with manure fertilizer, and (iii) with NPK fertilizer. Data was experimentally collected by planting chili in several plots treated by manure, with three replications. The field experiment was conducted in Gathak Village, Karangnongko Sub-district, Klaten District, Central Java. The data collected consist of the total population of Azotobacter and Azospirillum, nitrogen content in soil and the chili yield. The primary data of research were analyzed using ANOVA test and followed by LSD test, with the degree of significance by 95% .The results showed that the manure fertilizer can increase the population of bacteria as many as 0.02% (Azotobacter) and 0.46% (Azospirillum) when they were compared to the control one. So that it can increase the soil fertility when they were used in long time. Therefore increasing the nutrient availability in the soil was occurred. Application of manure fertilizer could increase the total nitrogen content in the soil and it is very useful for the fertilizing of plants.